2022
DOI: 10.1038/s43018-022-00336-7
|View full text |Cite|
|
Sign up to set email alerts
|

Radiation exposure elicits a neutrophil-driven response in healthy lung tissue that enhances metastatic colonization

Abstract: Radiotherapy is one of the most effective approaches to achieve tumour control in cancer patients, although healthy tissue injury due to off-target radiation exposure can occur. In this study, we used a model of acute radiation injury to the lung in the context of cancer metastasis, to understand the biological link between tissue damage and cancer progression. We exposed healthy mouse lung tissue to radiation prior to the induction of metastasis and observed a strong enhancement of cancer cell growth. We foun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
46
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 74 publications
(56 citation statements)
references
References 52 publications
3
46
0
Order By: Relevance
“…These different outcomes between CSF1R inhibition and MCP abolition can be partially attributed to the inefficacy of CSF1R-inhibitor in decreasing TAM numbers in GBM; therefore, no compensatory recruitment of neutrophils would be present. The results described here also suggest that compensatory neutrophil recruitment in monocyte-abolished tumors may reverse the synergizing effects of RT, similar to what was recently shown that locally activated neutrophils as a result of irradiation can create a tumor-supportive microenvironment in the lungs (Nolan et al, 2022).…”
Section: Genetic Deletion Of Qmcp Results In a Compensatory Influx Of...supporting
confidence: 88%
“…These different outcomes between CSF1R inhibition and MCP abolition can be partially attributed to the inefficacy of CSF1R-inhibitor in decreasing TAM numbers in GBM; therefore, no compensatory recruitment of neutrophils would be present. The results described here also suggest that compensatory neutrophil recruitment in monocyte-abolished tumors may reverse the synergizing effects of RT, similar to what was recently shown that locally activated neutrophils as a result of irradiation can create a tumor-supportive microenvironment in the lungs (Nolan et al, 2022).…”
Section: Genetic Deletion Of Qmcp Results In a Compensatory Influx Of...supporting
confidence: 88%
“… 186 Smad4 degradation blocks TGF-β signaling to inhibit lung metastasis, 187 to envisage the importance of TGF-β-mediated preconditioning for lung metastasis. Neutrophils on the other hand, facilitate lung metastasis by preconditioning the lungs through IL-5, GM-CSF, 188 lipocalin-2 ( LCN2 ), 189 and notch signaling 190 (Fig. 4 ).…”
Section: Preconditioning the Metastatic Niche Vs Preconditioning The ...mentioning
confidence: 99%
“…Murine models helped to understand that TAN function affects not only primary tumor growth but also metastasis formation by a variety of mechanisms. In a model of acute radiation injury to the lung, locally activated neutrophils were key drivers of the tumor-supportive preconditioning of the lung TME, governed by enhanced regenerative Notch signaling, which, in turn, augmented a stemness phenotype ( 117 ). In addition, neutrophils can support lung colonization of metastasis-initiating cancer cells by producing arachidonate 5-lipoxygenase–derived leukotrienes that aid the colonization of distant tissues by selectively expanding metastasis-initiating cancer cells ( 118 ).…”
Section: Tumor-infiltrating Myeloid Cells In Nsclcmentioning
confidence: 99%